MODEL ADOPTION BLENDED LEARNING: A STUDENT-CENTRIC EVALUATION IN ACCOUNTING EDUCATION - Suhartono, Entot; Purwantoro, Purwantoro (Assets: Jurnal Akuntansi dan Pendidikan, 2024)
ABSTRACT This study aims to develop a conceptual model of the behavioral interest of accounting students in adopting blended learning by combining the technology acceptance model and the theory of planned behavior, along with validating explanatory variables such as perceived usefulness, perceived ease of use, learning attitudes, subjective norms, and behavioral control. The study sample consists of accounting students in Semarang, with structural equation modeling used as the analytical tool. It was found that perceived ease and behavioral control did not impact learning attitudes, while perceived usefulness and subjective norms also showed no effect. The intention to adopt blended learning is influenced by perceived ease, learning attitudes, subjective norms, and behavioral control but not by perceived usefulness. Learning attitudes serve as a mediator between the effects of perceived ease and behavioral control on students' intention to adopt blended learning. ABSTRAK Penelitian ini bertujuan untuk mengembangkan model konseptual terkait minat mahasiswa akuntansi dalam mengadopsi blended learning dengan menggabungkan model penerimaan teknologi dan teori perilaku terencana. Penelitian ini juga berusaha memvalidasi variabel-variabel penjelas seperti persepsi manfaat, persepsi kemudahan, sikap belajar, norma subjektif, dan kontrol perilaku. Sampel yang digunakan adalah mahasiswa akuntansi di Kota Semarang, dengan menggunakan model persamaan struktural sebagai alat analisis. Hasil penelitian menunjukkan bahwa persepsi kemudahan dan kontrol perilaku berpengaruh terhadap sikap belajar, sementara persepsi manfaat dan norma subjektif tidak memiliki pengaruh. Minat dalam mengadopsi blended learning dipengaruhi oleh persepsi kemudahan, sikap belajar, norma subjektif, dan kontrol perilaku, kecuali persepsi manfaat. Sikap belajar berperan sebagai mediator dalam hubungan antara persepsi kemudahan dan kontrol perilaku dengan minat mahasiswa untuk mengadopsi blended learning.